2007
DOI: 10.1007/s10725-007-9193-z
|View full text |Cite
|
Sign up to set email alerts
|

Sugar effects on early seedling development in Arabidopsis

Abstract: Sugars affect a broad variety of processes, from growth and development to gene expression. Although it has already been shown that sugars act as signaling molecules, little is known about the mechanisms by which plants respond to them. Much progress has been made on understanding sugar sensing and signaling thanks to the analysis of mutants with abnormal sugar response. Some of the genetic strategies applied are based on the inhibitory effect of sugar on post-germinative development of Arabidopsis thaliana. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 91 publications
1
36
0
Order By: Relevance
“…The analysis of several sugar-sensing mutants reveals that the developmental arrest triggered by sugars is largely independent of the osmotic effects. Furthermore, recent studies have also highlighted that the sugar-sensing processes are uncoupled from the role of sugars as nutrients (Rognoni et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of several sugar-sensing mutants reveals that the developmental arrest triggered by sugars is largely independent of the osmotic effects. Furthermore, recent studies have also highlighted that the sugar-sensing processes are uncoupled from the role of sugars as nutrients (Rognoni et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that this process is closely associated with plant hormone biosynthesis and signalling, in particular with that of ABA (for review see Finkelstein and Gibson, 2001; Gazzarini and McCourt, 2001; León and Sheen, 2003;Rook et al, 2006;Dekkers and Smeekens, 2007;Rognoni et al, 2007). Mutants that were insensitive to the inhibiting effect of glucose and sucrose on early seedling development were isolated by several groups and identified ABA deficient mutants (i.e.…”
Section: The Genetic Control Of Seed Storage Compounds Seed Deteriormentioning
confidence: 99%
“…Because mutants in sugar sensing often exhibit seed germination phenotypes Gibson, 2005;Price et al, 2003;Rognoni et al, 2007), we also evaluated the sugar and ABA sensitivity of germination in the xlg triple mutant (Figure 7b). At low sugar concentrations (1% or 3%), germination of the xlg triple mutant was statistically identical to wild type with all sugars tested, including sucrose.…”
Section: Xlgs Are Negative Regulators Of Primary Root Lengthmentioning
confidence: 99%